Prognostic Value of Right Atrial Analysis in Patients With Nonischemic Cardiomyopathy - Lozano-Torres, Jordi; Ródenas-Alesina, Eduard; Tobías-Castillo, Pablo Eduardo; Badia-Molins, Clara; Vila-Olives, Rosa; Calvo-Barceló, Maria; Casas, Guillem; Soriano-Colomé, Toni; San Emeterio, Aleix Olivella; Sao-Avilés, Augusto; Fernández-Galera, Rubén; Méndez-Fernandez, Ana B.; et al. (Journal of the American Society of Echocardiography, 2025)
Right ventricular (RV) function is associated with a worse prognosis in patients with nonischemic cardiomyopathy (NICM), yet its evaluation may be challenging. Right atrial volume index (RAVI) and peak right atrial strain (PRAS) may reflect worse RV diastolic function, but their ability to identify patients at higher risk to predict clinical events among those with NICM has not been determined. The aim of this study was to investigate the value of right atrial strain analysis (RAVI and PRAS) in predicting cardiovascular mortality or heart failure hospitalization in a population of patients with NICM. This was a retrospective, single-center, observational, longitudinal study. Patients with NICM with left ventricular ejection fractions <50% and without coronary disease were included, irrespective of atrial rhythm. The primary end point was major adverse cardiovascular events (MACE), a composite of heart failure hospitalization or cardiovascular death. Five hundred twelve patients were included. MACE occurred in 134 patients (26.2%) during a median follow-up period of 3.4 years. Multivariable analysis, including right atrial and RV echocardiographic parameters, identified an increase in RAVI (HR, 1.07 for a 5 mL/m2 increase; 95% CI, 1.01-1.13; P = .019) and a decrease in PRAS (HR, 0.84 per 5% increase; 95% CI, 0.71-0.99; P = .034) independently associated with MACE, with an additive value (increase in Harrell’s C = 0.033, P = .043). RAVI remained associated with MACE after a Cox regression adjusted for age, hypertension, chronic kidney disease, and peak left atrial strain, with an HR of 1.05 for a 5 mL/m2 increase in RAVI (95% CI, 1.01-1.10; P = .025). Among patients with NICM, a larger RAVI identifies those at higher risk for cardiovascular death or heart failure hospitalization. PRAS provides additive value to RAVI when assessing the risk for MACE in this population. [Display omitted] •RAVI is associated with MACE in NICM.•PRAS provides additional value when assessing the risk for MACE.•The association of RAVI and MACE remains significant after multivariate analysis.•This highlights the clinical value of RA echocardiographic measures in NICM.